The Nature of Food Commodity Prices Volatility in Driving Inflation and Policy - Nurliza Nurliza (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The objective of research is to analyze the volatility effect of food commodity prices and whether surging food commodity prices have spilled over into food inflation and total inflation with time series data through Box-Jenkins method for 12 food commodity prices. The results have proved that only beef price had high volatility effects and have asymmetric effect. While, soybeans, cooking oil, and food are vulnerable but did not have volatility effects. The change in food commodity prices are significant drive the inflation in the long-term although in the short-term insignificant. The government needs to overcome the full transmission effect of an exogenous shock and to introduce economic reform through investment, infrastructure, and markets for corn and egg for food inflation; eggs and peanuts for total inflation. Besides, strong second-round effects of higher commodity prices on inflation have generally been absent converged to core inflation.DOI: 10.15408/sjie.v6i1.4523